Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


We know that 
( a+b)^{2} -(a-b)^{2} =4ab
so  (4pq+3q)^{2} -(4pq-3q)=4(4pq)(3q
=48p q^{2}
                                                  hope i helped you
4 4 4
(4pq+3q)²=16(pq)^2+24pq^2+9q^2(4pq-3q)²=16(pq)^2-24pq^2+9q^2therefor (4pq+3q)²-(4pq-3q)²=48pq^2
2 4 2
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts